Iron catalyzed ketoalkylation and ketoalkylation/etherification of styrenes initiated by selective C–C bond cleavage. Issue 17 (27th July 2020) - Suo, Meng-Ting; Yang, Shuo; Yang, Jun-Cheng; Liu, Ze-Yu; Zhang, Jun-Jie; Guo, Li-Na
Abstract : A mild and efficient iron-catalyzed ketoalkyl-Heck-type coupling initiated by radical C–C bond cleavage is described. Furthermore, this concise catalytic system was also applicable for the three-component ketoalkylation/etherification of styrenes. Abstract : An iron-catalyzed ketoalkyl-Heck-type coupling initiated by radical C–C bond cleavage is described. The features of this protocol include mild conditions (40 °C, free of ligands and bases), broad substrate scope, excellent functional group tolerance and stereoselectivity. Satisfactorily, this Fe-based catalytic system was also applicable for the three-component ketoalkylation/etherification of styrenes.